G6PD deficiency in Malaysia’s Proto-Malay Orang Asli indigenous population: A molecular and epidemiological study - Mohamed Afiq Hidayat Zailani; Raja Zahratul Azma Raja Sabudin; Muhammad-Redha Abdullah-Zawawi; Azlin Ithnin; Hafiza Alauddin; Siti Aishah Sulaiman; Najiah Ajlaa Ayub; Rinie Awai@Albert; Muhammad Dinie Afif Jamaludin; Muhammad Ziqrill Mohd Zapri; Ainoon Othman (PLoS ONE, 2025)
Glucose-6-phosphate dehydrogenase deficiency (G6PDd) is one of the most common genetic disorders worldwide and remains highly prevalent in malaria-endemic regions. Individuals with G6PDd are at risk of severe complications, including acute haemolytic anaemia, when exposed to oxidative triggers. In Malaysia, the Proto-Malay Orang Asli (PMOA), the second largest indigenous group in Peninsular Malaysia, represents a vulnerable population. This study aimed to estimate the prevalence and mutation spectrum of G6PDd in this community. A total of 258 peripheral blood samples (91 males, 167 females) were screened using a quantitative G6PD assay (OSMMR2000-D). DNA from 73 samples was genotyped with the Hybribio G6PD GenoArray test, and 39 underwent targeted sequencing. The adjusted male median (AMM) of G6PD activity was 9.6 U/gHb (95% CI: 8.9–10.3 U/gHb), with 30% and 80% thresholds corresponding to 2.9 and 7.7 U/gHb, respectively. At the 30% cut-off threshold, the overall estimated prevalence of G6PDd was 6.8% (16/237; 12 males and 4 females). A total of 21 subjects were G6PD-intermediate (7 males and 14 females), and the remaining 221 subjects were G6PD-normal (72 males and 150 females). Genotyping identified 18 hemizygous males, 13 heterozygous females, and 3 homozygous females. Five G6PD variants were detected: G6PD Viangchan (39.5%), G6PD Coimbra (28.9%), G6PD Union (23.7%), G6PD Kaiping (5.3%), and rs782038151 (2.6%). This study demonstrates that G6PDd is common in the PMOA population, with notable molecular diversity. These findings have important implications for malaria control and the safe use of antimalarial drugs in this high-risk community.